Global Economic Prospects, June 2010 : Fiscal Headwinds and Recovery - World Bank (Washington, DC, 2013)
Market nervousness concerning the fiscal positions of several European high-income countries poses a new challenge for the world economy. This arises as the recovery is transitioning toward a more mature phase during which the influence of rebound factors (such as fiscal stimulus) fades, and gross domestic product (GDP) gains will increasingly depend on private investment and consumption. So far evolving financial developments in Europe have had limited effects on financial conditions in developing countries. Although global equity markets dropped between 8 and 17 percent, there has been little fallout on most developing-country risk premia. And despite a sharp deceleration in bond flows in May, year-to-date capital flows to developing countries during the first 5 months of 2010 are up 90 percent from the same period in 2009. The economic impact on long-term growth in developing countries of a forced pullback from growth-enhancing infrastructure and human-capital investment due to lower fiscal revenues, weaker official development assistance (ODA), and sluggish capital flows, are difficult to gauge, as are the effects on private sector growth of tighter financial sector regulations, and increased competition for capital from high-income sovereigns. Global economic prospects: crisis, finance and growth estimated that just the latter two factors could reduce developing country growth rates by between 0.2 and 0.7 percent for a period of 5 to 7 years.